Transforming to a Multinational Cultural Organization: Strategical Change in the Safety and Environmental Aspects and its Regulation in Hazardous Chemicals Handling Industry - Alavandar, Yudhistra Kumar (Universitas Negeri Semarang, 2025)
The strategic cultural shift implemented by the multinational company (MNC) has significantly advanced the organization’s Environmental Health and Safety (EHS) objectives compared to previous management practices. These cultural changes have fostered a stronger safety culture and enhanced environmental protection. By employing both qualitative and quantitative data collection methods, the study highlights key strategic initiatives that contributed to these improvements. Notable advancements include the introduction of an online safety training platform, which increased occupant safety awareness, and the implementation of an online work permit system for better activity tracking. The adoption of a three-dimensional safety approach has strengthened process safety management, while environmental monitoring has improved through online pollutant tracking and biweekly leak detection tests to reduce fugitive emissions. Overall, the transformation in organizational culture under MNC leadership has elevated safety and environmental consciousness across the workforce.